A long-term conditional survival analysis for gastric cancer based on 7th and 8th TNM classification in Eastern and Western populations. Issue 12 (December 2018) - Chen, Qi-Yue; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Chang-Ming
Abstract: Background: To compare the power to predict the 5-year conditional disease-specific survival (CS5) between the 7th and 8th editions of the TNM for gastric cancer (GC) patients. Method: This retrospective study recruited 20, 548 patients who underwent GC surgery from the databases of the Surveillance, Epidemiology, End Results and a center in Asia. The CS5 was evaluated with the 7th and 8th TNM classification. Results: A two-step model showed that at the 3-5th postoperative years, the 8th staging remained an independent risk factor, whereas there was no significant difference for 7th -edition staging. Further analysis of the ability to predict CS5 indicated that there were significant differences in the CS5 of 7th -edition stages IIb and IIIa at baseline and at the postoperative 1-4th years (all p < 0.05, Cohen's d > 0.5). However, the CS5 of the fifth year was similar between them (p = 0.307, Cohen's d = 0.35). Meanwhile, the results indicated that the 8th -edition staging could effectively determine the CS5 among stages Ⅰa, Ⅰb, Ⅱa, Ⅱb, Ⅲa, and Ⅲb at baseline and at the postoperative 1-5th years (all p < 0.05). However, neither the 7th - nor the 8th -edition staging could predict the CS5 for stages Ⅲb and Ⅲc from the postoperative third to fifth years (all p > 0.05). Conclusions: For patients with stages IIB and IIIA GC, the 8th TNM has a higher discriminatory value than the 7th edition for CS5 after the postoperative fourth year. However, a more detailed classification system is still needed to predict conditional survival for GC.